The effect of risk leverage on investors’ preferences in manufacturing companies listed on the Indonesia Stock Exchange - Intan Shaferi (Investment Management & Financial Innovations, 2018)
Financial resources have become one of the funding policies considered by companies. The financial resources can come from internal and external sources. Leverage is used as one of the policies to get external source of funds. By using leverage, companies have additional funds that can be used for their operations and investments. When a company decided to use leverage as a financing policy, it is expected to get enough funds to finance its business. Raising the funds will lead to better company’s financial performance. However, on the other hand, by raising funds, the company also needs to consider the risks. Thus, leverage is related to risk. Then, risk is one of the considerations for investors to think about.This research aims to examine the effect of risk leverage and hopefully can give illustration for investors in analyzing the risks of investors’ preferences. Besides, other variables used are size and profitability. These two variables are also the ground for considering risks. With pooled data analysis, this research was conducted on manufacturing companies listed on the Indonesia Stock Exchange during the five-year period from 2012 until 2016. The result shows that leverage, profitability and size have significant effects on risk.